Psychosocial aspects of gender violence and its incidence in femicide: a systematic review (Revista Estudios Psicológicos, 2024)
Introduction: research in the field of gender violence and femicide indicates a marked interest on the part of collectives, professionals, and entities working in defense of human rights. The risk factors associated with this phenomenon have psychological, social, political, and economic repercussions that have contributed to gender inequality and discrimination based on the norms of patriarchal cultures. Methodology: a systematic review of the literature was conducted using Boolean equations, searching across three databases (Proquest, ebscohost, and Wos Clarivate). Results: it was found that various forms of violence against women increase the likelihood of behavioral alterations, as well as anxiety, depression, post-traumatic stress, or psychotic disorders. Moreover, various social, economic, and cultural barriers embedded in society limit the eradication of this issue. Conclusions: gender violence has physical and mental effects that negatively impact the comprehensive health of the victims, affecting short, medium, and long-term mental stability and diminishing quality of life.
Keywords: gender violence; feminice; abuse; discrimination; inequality